MODEL PENGELOLAAN PENYIARAN DIGITAL (STUDI KASUS PADA PERSIAPAN ANALOG SWITCH OFF 2022 DI PROVINSI RIAU) - Yasir; Suyanto; Setiawan, Hisam (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
This study aims to find out an overview of the digital broadcasting management model with a case study on the preparation of Analog Switch Off (ASO) or the migration of analog to digital television in Riau Province which will take place on November 2, 2022. The preparation of the Television of the Republic of Indonesia (TVRI) Riau as the manager of digital television multiplexing and the readiness of the community to receive digital television broadcasts in Riau Province are the main focus. This study uses a descriptive qualitative approach with case study research methods through interviews and observation data collection techniques. The results show that the digital broadcasting management model in Riau Province takes into account several indicators (a). Digital Broadcasting Quality (digital television multiplexing infrastructure), (b). Choice of Broadcast Program (digital television broadcast program) (c). Device Support (digital broadcast receiving device ecosystem – Set Top Box) and (d). Public knowledge (socialization to the community) is still not optimal in an effort to support the preparation for the implementation of Analog Switch Off (ASO) in Riau Province.